2021
DOI: 10.1080/14658011.2021.1898880
|View full text |Cite
|
Sign up to set email alerts
|

Passive cooling performance of polyacrylamide hydrogel on wooden and brick houses and effect of nanoparticle integration on its mechanical strength

Abstract: Thermoresponsive hydrogels have been studied in the past as self-healing and ultra-porous materials. Single-network (SN) and double-network (DN) hydrogels were synthesised in this research using acrylamide, acrylic acid, and alginate. Nano reinforcements were added only to increase the mechanical strength which is reported up to 300%. These DN hydrogels showed brilliant cooling performance showing 8-12°C lesser in a coated house for over 7 h with a single hydration cycle. Tough hydrogels were tested under dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The structure has the potential for food and drug preservation and the temperature regulation of building structures in areas with limited power resources. Another study provided by Arslan et al [48] found that polyacrylamide hydrogels can effectively cool timber structures and masonry houses without relying on active cooling. They enhanced the mechanical strength of the hydrogels by adding nanoparticles and found that dual-network hydrogels provided better strength and cooling over extended periods of time.…”
Section: Building Energy Consumption Savingmentioning
confidence: 99%
“…The structure has the potential for food and drug preservation and the temperature regulation of building structures in areas with limited power resources. Another study provided by Arslan et al [48] found that polyacrylamide hydrogels can effectively cool timber structures and masonry houses without relying on active cooling. They enhanced the mechanical strength of the hydrogels by adding nanoparticles and found that dual-network hydrogels provided better strength and cooling over extended periods of time.…”
Section: Building Energy Consumption Savingmentioning
confidence: 99%